A novel device combining acoustic vibration with oscillating expiratory pressure for the treatment of nasal congestion. Issue 5 (27th February 2020) - Soler, Zachary M.; Nguyen, Shaun A.; Salvador, Craig; Lackland, Thomas; Desiato, Vincent M.; Storck, Kristina; Schlosser, Rodney J.
Abstract : Background: Chronic nasal congestion affects 20% of the population with significant impact on quality of life. This study investigated the simultaneous administration of nasal acoustic vibration and oscillating expiratory pressure for the treatment of nasal congestion. Methods: Patients with chronic nasal congestion but without fixed anatomic obstruction participated in a prospective clinical study applying simultaneous acoustic vibrations and positive expiratory pressure to the nasal cavity twice daily over 5 weeks. Safety was assessed by rhinoscopy and patient questionnaires. Efficacy was assessed using peak nasal inspiratory flow (PNIF), visual analogue scale (VAS) of nasal symptoms, Total Nasal Symptom Score (TNSS), Nasal Obstruction and Septoplasty Effectiveness (NOSE) score, and the 22‐item Sino‐Nasal Outcome Test (SNOT‐22). Results: Forty patients (mean age 39 years, 65% female) completed the study with no adverse effects. At the 2 week follow‐up, PNIF improved by 25.0 L/min (31% increase from baseline, p < 0.001). At the 5 week follow‐up, nasal congestion VAS improved from mean ± SD of 5.8 ± 2.4 to 2.6 ± 2.3, TNSS improved from 7.2 ± 3.5 to 3.5 ± 3.1, NOSE improved from 50.4 ± 19.9 to 23.3 ± 17.2, and SNOT‐22 improved from 31.7 ± 20.3 to 14.2 ± 12.7, all p < 0.001. Eighty percent of patients would use the device again and 87.5% would recommend to others. Conclusion: Simultaneous administration of acoustic vibration and oscillating expiratory pressure appears to be a safe treatment for chronic nasal congestion. Results from this initial study are promising with regard to efficacy but will require further study.